Inventarisasi Tanaman Pangan pada Pekarangan Masyarakat Lokal Papua di Distrik Heram, Kota Jayapura - Nelly Lunga; Maria L. Simonapendi (Jurusan Biologi FMIPA Universitas Cenderawasih, 2017)
The aim of this study was to understand the plant species grown in house yard of local people in Heram District which had been used as food by local people and the potential of those plant to be and income sources for local people. This research was conducted from August 2016–April 2017 using survey and laboratory analysis. Purposive sampling was used to determine the sample, and from 5 villages 5 house yard will be selected to be the sample (total 25 house yard). From this study we found that there were 45 species from 33 family of plants which used as vegetables, ingridients, fruits, and mainly foods.Key words: tanaman pangan, masyarakat lokal, Papua